Identification and validation of potential flood hazard area using GIS‐based multi‐criteria analysis and satellite data‐derived water index. Issue 3 (6th May 2020) - Dash, Pratik; Sar, Jishnu
Abstract: This article identifies potential flood hazard areas through multi‐criteria analysis in Allahabad district, India. The study has incorporated eight criteria, namely, flow accumulation, draining capability, elevation, groundwater depth, land use, runoff coefficient, slope, and geology for preparing hazard index. The weights of the criteria were obtained through the analytical hierarchy process (AHP) method based on their relative importance for occurring floods. Finally, a flood hazard index (FHI) was prepared by combining the parameter ratings and corresponding weights. The credibility of the present methodology was tested through validation with the satellite‐based inundation map of August 20, 2016. A normalized difference water index (NDWI) was prepared from Landsat‐8 OLI data and the inundated area was delineated by a binary classification of NDWI based on a threshold calculated following Otsu's method. The analysis found 81% of inundation is associated with high to very high flood hazard zones. Agricultural land is more prone to flood than other land use types. The results showed that the GIS‐based multi‐criteria analysis framework could be effectively applied for flood hazard analysis to support decision making in disaster management.